Development of Student Worksheets with Canva App-Assisted Problem Based Learning Models to Improve Skills Mathematical Literacy of Junior High School Students - Nurazizah, Nurazizah; Putri, Jihan Hidayah (Journal of Community Research and Service, 2024)
The purpose of this study is (1) to determine the validity, practicality and effectiveness  of Student Worksheets with the developed PBL Model (2) To find out how Student Worksheets (LKPD) with the Problem Based Learning (PBL) model assisted by Canva can improve the mathematical literacy skills of grade VIII students of SMPS Al washliyah 8 Medan. This research method is research development (Research and Development) using the ADDIE model. The subject of this study is a grade VIII student of SMP Al washliyah 8 medan for the 2023/2024 academic year. The learning LKPD developed has met the criteria of validity, practicality and effectiveness. Reviewed for validity, the average value of total LKPD validation was 4.42 (very valid), then the total validity of RPP was 4.47 (very valid) and as well as mathematical literacy ability tests, student response questionnaires and practical questionnaires were declared valid. Judging from practicality: the average value of practicality from trial I from teachers was 82% (practical) and student responses were 81.83% (practical). In trial II from teachers by 95% (practical) and student responses 86.83 (practical). Judging from effectiveness, with the student worksheet (LKPD) developed, the average score increased from test I of 71.43 to 89.28 in trial II.